PENGARUH PRODUKTIVITAS DAN PERTUMBUHAN PERUSAHAAN PADA PERINGKAT OBLIGASI DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Dewi, Putu Yulia Pransiska; Suaryana, I Gusti Ngr. Agung (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
This bond rating is crucial because said rank represent informative statement and gives out signal about the failure of the company debt. The purpose of this research is to examine the effect of company productivity and growth on bond rating, examine size company  in moderating company productivety and growth on bond rating. The object of this research is size company as the moderator of the effect company productivity and growth on bond rating in manufacture company that are listed in Bursa Efek Indonesia (BEI) 2010-2015 and was ranked by PT. PEFINDO. The amount of sample used are 49, using purposive method, data analysis technique using moderated regression analysis (MRA). the result of this research shows company productivity and growth have a positive on bond rating, size company could moderating the effect of company productivety and growth on bond rating
Keywords: productivity, growth, size company, bond rating